Reading Interest of Literacy Taman Membaca Visitor at Penujak Village Lombok Tengah - Tawali, Tawali (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This study aims to describe the level of reading interest of visitors to the Reading Park located in Penujak Village, West Praya District, Central Lombok Regency.The literacy of this reading park with the aim of educating the community that the importance of reading and the importance of literacy as a reference to increase knowledge This research used a qualitative method with a descriptive qualitative to design research and data obtained with research that is prepared qualitatively. The data collection technique, in this study, used four steps, namely interview, recording, and shooting. The interviews used are freely guided interviews, in this study the researcher conducted interviews twice a day in depth, the first interview started at 08.00 to 12.30, and the second interview started at 02.00 to 06.00. In one day, it takes two to four interviews. From the results of the interviews conducted, it is known that the total number of visitors for one week was 116 visitors. However, only 13 visitors were participants, the visitors came from different social statuses, different ages, and different villages. The Data Analysis procedures used are data reduction, data display, and conclusion and verification. The results of this study show that all visitors in Reading Park Literacy have an interest in learning, From the results obtained, it can be seen that reading interest in Reading Garden Literacy is the highest among children.